Building collaborative practice through interprofessional education: music therapy and nursing students engaged in collaborative research. (1st June 2016) - Robb, Sheri L.; Hanson-Abromeit, Deanna
Abstract : Background : The health care landscape is changing, with greater emphasis on the need for integrative care that is delivered by multi-professional teams. This has resulted in the emergence of Interprofessional Education (IPE) which is a collaborative learning process that affords students from different disciplines opportunities to learn about and with each other, for the purpose of building stronger interdisciplinary collaborations and improving patient outcomes. Objective : Describe an innovative, cross-institutional undergraduate research program involving students from two professions. We provide an overview of: (1) IPE including initiatives from the World Health Organization and educational Core Competencies, (2) student research project and corresponding IPE elements, and (3) student/faculty perspectives about the IPE experience. Methods : Music therapy and nursing students are conducting a large systematic review of music intervention research to identify and describe intervention content, outcomes of interest, interventionist qualifications, and terminology. Discussion : Students have gained direct experience with IPE Core Competencies: values/ethics, roles/responsibilities, interprofessional communication, and teams/teamwork. We discuss program strengths/limitations and provide recommendations. Conclusions : IPE experiences prepare students for collaborative practice in the workplace.